2018
DOI: 10.15520/ijcrr/2018/9/04/500
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity Endorsement as Moderating Variable on the Relationship between Loyalty and Corporate Credibility of Travel Companies in Aceh

Abstract: To increase customer loyalty, travel companies in Aceh use celebrity endorsement to help promote their products. The purpose of this study was to examine important criteria in creating customers’ loyalty. The effect of celebrity endorsement as moderating variabel on the relationship between loyalty and corporate credibility are investigated for this purpose. A sample was drawn from umrah pilgrims in Aceh with 220 respondents. Primary data was used in this study in form of questionnaire with Likert scale. SPSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Apart from that, the ustadz is a figure who has high knowledge in the religious field and is considered very suitable for promoting Umrah travel agencies. Therefore, many Umrah travel agents use ustadz for endorsements (Alfanda, et al, 2018). Nevertheless, based onThe results of interviews with Tridaya Tour and Travel managers revealed that Tridaya Tour and Travel only implemented the Ustad endorsement strategy after the Kingdom of Saudi Arabia opened Umrah travel in Mecca.…”
mentioning
confidence: 99%
“…Apart from that, the ustadz is a figure who has high knowledge in the religious field and is considered very suitable for promoting Umrah travel agencies. Therefore, many Umrah travel agents use ustadz for endorsements (Alfanda, et al, 2018). Nevertheless, based onThe results of interviews with Tridaya Tour and Travel managers revealed that Tridaya Tour and Travel only implemented the Ustad endorsement strategy after the Kingdom of Saudi Arabia opened Umrah travel in Mecca.…”
mentioning
confidence: 99%